Definition of erythroid cell‐positive blood transcriptome phenotypes associated with severe respiratory syncytial virus infection. Issue 8 (12th December 2020) - Rinchai, Darawan; Altman, Matthew C.; Konza, Oceane; Hässler, Signe; Martina, Federica; Toufiq, Mohammed; Garand, Mathieu; Kabeer, Basirudeen Syed Ahamed; Palucka, Karolina; Mejias, Asuncion; Ramilo, Octavio; Bedognetti, Davide; et al.
Abstract: Biomarkers to assess the risk of developing severe respiratory syncytial virus (RSV) infection are needed. We conducted a meta‐analysis of 490 unique profiles from six public RSV blood transcriptome datasets. A repertoire of 382 well‐characterized transcriptional modules was used to define dominant host responses to RSV infection. The consolidated RSV cohort was stratified according to four traits: "interferon response" (IFN), "neutrophil‐driven inflammation" (Infl), "cell cycle" (CC), and "erythrocytes" (Ery). We identified eight prevalent blood transcriptome phenotypes, of which three Ery+ phenotypes comprised higher proportions of patients requiring intensive care. This finding confirms on a larger scale data from one of our earlier reports describing an association between an erythrocyte signature and RSV disease severity. Further contextual interpretation made it possible to associate this signature with immunosuppressive states (late stage cancer, pharmacological immunosuppression), and with a population of fetal glycophorin A+ erythroid precursors. Furthermore, we posit that this erythrocyte cell signature may be linked to a population of immunosuppressive erythroid cells previously described in the literature, and that overabundance of this cell population in RSV patients may underlie progression to severe disease. These findings outline potential priority areas for biomarker development and investigations into the immune biology of RSV infection. The approach that we developed and employed here should also permit to delineate prevalent blood transcriptome phenotypes in other settings. Abstract : Immune determinants of respiratory syncytial virus (RSV) disease severity remain ill‐defined. We conducted a meta‐analysis of six public RSV blood transcriptome datasets. Severe patients molecular phenotypes presented traits associated with immunosuppressive states and extramedullary erythropoiesis signatures.